The study of initial permeability temperature dependences for LiTiZn ferrite ceramics; IOP Conference Series: Materials Science and Engineering; Vol. 289 : Modern Technologies for Non-Destructive Testing - Petrova A. B. Anna Borisovna (2018, 2018)
Title screen